Poorer Cognitive Performance in Patients with Essential Tremor-Parkinson’s Disease vs. Patients with Parkinson’s Disease - Louis, Elan D.; Rohl, Brittany; Collins, Kathleen; Cosentino, Stephane (Frontiers in Neurology, 2015)
Background: Patients with essential tremor (ET) seem to be at increased risk of developing Parkinson’s disease (PD). Surprisingly little has been written about this clinical entity, ET-PD. Cognitive dysfunction is a well-known feature of PD, and can also be an issue in patients with ET. Whether the presence of the combined diagnosis, ET-PD, is associated with additive cognitive effects as compared with PD, has not been studied. Methods: Thirty ET-PD patients and 53 age-matched PD patients were enrolled in a clinical-epidemiological study. Two cognitive screens, the Telephone Interview for Cognitive Status (TICS, score = 0 – 41) and Folstein Mini-Mental State Examination (MMSE; range 0 - 30), were administered. Results: The MMSE score was lower in ET-PD than PD (26.5 ± 3.1 [median 28.0] vs. 28.4 ± 2.2 [median 29.0], p = 0.001). The TICS score was lower in ET-PD than PD (31.7 ± 3.9 [32.0] vs. 35.0 ± 2.0 [35.0], p<0.001). Subscores of these tests that related to orientation (p<0.001), language (p<0.001) and working memory (p = 0.001) were lower in ET-PD than PD, whereas the delayed memory subscore was only marginally lower in ET-PD than PD (p = 0.06), and the two groups did not differ with respect to the motor/construction subscore (p = 0.22). Both global cognitive scores were inversely correlated with disease duration (for MMSE score, Spearman’s r = -0.46, p<0.001; for TICS score, Spearman’s r = -0.53, p<0.001). Conclusions: The combined diagnosis, ET-PD, seemed to be associated with additive cognitive effects as compared with PD alone.